Individual Performance of CIMC Staff Nurses and Patient Satisfaction: its Relationship in Maintaining Quality Standards of Care - Alvarado, Angelito Estoesta; Ablao, Gloria Ortiz (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
This study aims to examine the relationship between the Individual Performance Commitment and Review (IPCR) of CIMC (City of Ilagan Medical Center) staff nurses and patient satisfaction in maintaining the quality standards of care using a descriptive quantitative approach. The research focuses on measuring the extent to which nurses' performance evaluations, as reflected in their IPCRF scores, correlate with the satisfaction levels reported by patients regarding the care they received. Data were collected through structured surveys distributed to both staff nurses and patients. The IPCRF scores of nurses were analyzed alongside patient satisfaction surveys to identify patterns and relationships. Descriptive statistics, such as mean scores and frequency distributions, were used to analyze the data and provide an overview of the current state of performance and satisfaction. The results highlight a positive correlation between high performance ratings of staff nurses and greater patient satisfaction. This study contributes valuable insights into the role of performance evaluations in healthcare quality, suggesting that improving nurse performance through regular assessments may enhance patient care outcomes. The findings have implications for healthcare institutions looking to improve the quality of care by refining performance management systems for nursing staff.